DETERMINATION OF THE OPTIMAL POWER RANGE OF TRACTION FUNDS FOR PASSENGER TRANSPORT ON THE GROUND TRACTION - Hetman, H. K.; Arpul, S. V.; Dovhan, E. O. (Science and Transport Progress, 2005)
A method of determining optimal power range of tractive vehicles for passenger operations in case of applying several speed categories on traction area of a locomotive depot or a railroad has been developed.